Synergistic effect of nickel nanoparticles and carbon nanotubes buckypaper for enhancement of microwave shielding properties - Sukgorn, Nuttaya; Yordsri, Visittapong; Thanachayanon, Chanchana; Horprathum, Mati; Chudpooti, Nonchanutt; Akkraekthalin, Prayoot; Chalapat, Khattiya; Wongwiriyapan, Winadda (My University, 2020)
Carbon nanotubes (CNTs) are considered as the most promising materials to solve the electromagnetic interference (EMI) issue. Various forms of CNTs including CNTs/polymer composites, metal nanoparticles-decorated CNTs and freestanding CNT buckypapers (CNT BPs) have been proposed to enhance shielding effectiveness. In this study, the synergistic effect of nickel nanoparticles (NPs) and relatively short CNTs for the enhancement of microwave shielding properties was investigated. CNT BPs were prepared by vacuum filtration of well-dispersed multi-walled CNTs and subsequently nickel was decorated on the CNT BPs (Ni/CNT) by pulsed DC sputtering technique with different deposition times of 0, 5, 10 and 15 min (hereinafter referred to as CNi0, CNi05, CNi10 and CNi15, respectively). The diameter of Ni/CNT increased from 8.74±0.53 to 72.5±3.2 nm and the conductivity improved from 9.57±0.87 to 12.57±0.59 S/cm when the nickel deposition time was 15 min. Nickel NPs were the mixed phases of nickel and nickel oxide with a dominant nickel phase. The shielding effectiveness at the frequency of 9.5 GHz achieved to-34.1 dB for CNi15. The enhancement of shielding effectiveness of CNi15 is attributed to the synergistic effect of CNTs and nickel NPs on wave dissipation.
Keywords: Carbon nanotubes; Microwave Shielding; Nickel; Sputtering